Neuroprotection effect of HSV-1 LAT-derived miR-H2 and miR-H3 associated with Tau and alpha-synuclein downregulation - Fatemeh Saadatpour; Zahra Fekrirad; S. Mohammadhadi Mirab; Pedram Mardani; Ehsan Arefian (Brain Research Bulletin)
Latency-associated transcript (LAT)-derived miRNAs are presumably the primary anti-apoptotic impellers and the other herpes simplex virus-1 (HSV-1) genes. However, the mechanisms by which this group of miRNAs negatively regulates apoptosis have not been fully elucidated. This study evaluated the hypothesis that LAT-derived miRNAs, specifically miR-H2 and miR-H3, serve as key regulatory effectors of LAT-mediated neuronal protection by targeting MAPT and SNCA, thereby interfering with caspase activation and apoptosis pathways. In silico analyses, along with in vitro and in vivo experiments, were conducted to identify key target genes of LAT-derived miR-H3 and miR-H2 and to evaluate their regulatory effects on MAPT and SNCA in sub-stable SH-SY5Y cells and latently HSV-1–infected mice, using quantitative real-time PCR (qRT-PCR) and Western blotting. The individual roles of miR-H2 and miR-H3 were investigated in vitro using luciferase reporter assays and a loss-of-function approach involving miRNA sponges. Additionally, the neuroprotective effects of LAT-derived miR-H2 and miR-H3 were evaluated through MTT and LDH assays, flow cytometry, and a quantitative analysis of apoptosis gene expression. It has been demonstrated that miR-H2 and miR-H3 overexpression directly target and suppress the expression of MAPT and SNCA genes, reducing their protein levels in the stable SH-SY5Y cells and during latency in TGs and Hip samples of mice. In addition, conditional miRNA sponge and luciferase assay approaches indicated the potential capacity of miR-H2 and miR-H3 to regulate MAPT and SNCA expression. Cells expressing miR-H2 and miR-H3 demonstrated an 80 % increase in viability and over 40 % enhancement in cell cycle progression, linked to the downregulation of MAPT and SNCA in SH-SY5Y cells. Significant alterations in CASP3 and BCL2 expression were observed in both cellular and mouse models, underscoring the anti-apoptotic effects associated with the negative regulation of caspase cascade inducers, Tau and α-syn, by miR-H2 and miR-H3. Considering the results, the neural survival prompted by LAT-derived miRNAs suggests a positive correlation between the disruption of MAPT and SNCA expression, affecting both anti-apoptotic and pro-apoptotic processes. Future studies investigating the neuroprotective properties of HSV-1 miRNAs, particularly their impact on multi-structural peptide deficiencies, will offer valuable insights into HSV-1–host co-evolution and mechanisms for counteracting neuronal apoptosis. In addition to endogenous miRNAs, LAT-derived miRNAs should also be regarded as promising candidates with significant therapeutic potential for managing the molecular mechanisms underlying disorders that lead to the onset and progression of neurodegeneration.